Don’t touch my no-no square / Isabel Adani Baderul Hisham and Mohd Izuan Ismail - Baderul Hisham, Isabel Adani; Ismail, Mohd Izuan (Academy of Language Studies, 2023)
‘Don’t touch my no-no square’, is a children’s pop-up book about the prevention of sexual harassment. This book is to enlighten the knowledge of one of the more taboo topics that have been a problem for centuries, by teaching the younger generation about sexual harassment, ways to avoid becoming a victim and to ask for help when needed. The process of making the book starts with deciding the target audience, drafting a story for the book, designing characters, making a prototype of the pop-up book, designing the actual product and promoting the final product. A questionnaire had been given to the public about their thoughts on the product and if it would be beneficial for the target audience. Based on the results, about 66 respondents answered the questionnaire and based on the results, 98.5% of them found that the book would do good for the children while the rest said otherwise.